Principal Transformational Leadership Strategies In Evidence Based Digital School Policy: Strategi Kepemimpinan Transformasional Kepala Sekolah Dalam Kebijakan Sekolah Digital Berbasis Bukti - Bachtiar, Iwan Candra; Rosalina Br. Ginting; Lilik Ariyanto (Academia Open, 2026)
General Background The acceleration of digitalization in educational governance requires comprehensive structural transformation in primary school management. Specific Background The transition toward integrated digital ecosystems frequently encounters systemic obstacles, including teacher resistance, infrastructure limitations, and inadequate managerial governance in utilizing educational platforms. Knowledge Gap While previous literature examines digital leadership broadly, empirical evidence regarding how public elementary principals operationalize evidence-based digital policies under resource constraints remains limited. Aims This study analyzes a principal’s transformational leadership strategies in planning, executing, and monitoring evidence-based digital school policies at Tabet Public Elementary School. Results Qualitative case study findings indicate the principal mitigated teacher resistance through digital role modeling and participatory decision-making. Infrastructure development was sustained through continuous technology asset auditing and strategic resource prioritization. Furthermore, the school transitioned to data-driven monitoring utilizing digital dashboards and established strict standard operating procedures for cyber security and data privacy. Novelty This research uniquely identifies the enforcement of cyber security regulations and data-driven e-portfolio monitoring as core organizational values within resource-constrained primary schools. Implications These managerial strategies provide a sustainable framework for elementary schools to cultivate secure, accountable, and adaptive digital governance ecosystems without relying on bureaucratic coercion. Highlights Digital role modeling and participatory decision-making mitigate teacher resistance toward technological transitions. Continuous technology asset auditing enables strategic infrastructure development despite financial resource constraints. Data-driven monitoring and strict cyber security protocols build secure and accountable organizational ecosystems. Keywords Digital School; Evidence Based Policy; Transformational Leadership; Educational Governance; Cyber Security